METHODOLOGICAL PRINCIPLES OF ASSESSING AND FORECASTING THE SOCIO-ECONOMIC DEVELOPMENT OF THE REGIONS (World Economics and Finance Bulletin, 2023)
Regional characteristics can be taken into account only in a comprehensive approach. At the moment, the importance of local authorities in the planning and coordination of the comprehensive socio-economic development strategy of the region will increase sharply. Today, local authorities do not have the function of coordinating the complex socio-economic development of the region and the necessary resources for its implementation. Transferring this function from the center to the regional level is, in effect, vertical decentralization. This process should include fiscal decentralization and giving regions the right to use a certain part of their resources independently. At the local level, the natural increase of the population, migration processes, the distribution of labor resources by employment sectors, health care, public education, cultural management, consumption of various services, housing construction and population settlement, construction, development of the industrial base, water and electricity supply, various communications it is possible to create an effective mechanism of regulation
Keywords: socio-economic development; business circles; special economic zones